Objectification and the Male Gaze: A Semiotic Analysis of Women's Representation in Tyla's Music Video Water - Haq, Rona Arinal; Yahdini, Azka Tsania (CHANNEL: Jurnal Komunikasi, 2024)
Women are often represented as objects in popular media, including music videos. This results in the subordination of women and the normalization of sexual harassment. This research focuses on examining the visuals displayed in Water Tyla's music video "Water", which features many women as passive objects of visual satisfaction, which is done using the male gaze shooting technique. The author is interested in conducting this research with the aim of finding out the representation of Male Gaze in Tyla's music video "Water" to analyze and show the sensual visuals of women who are objectified by men's power over women as symbolic violence and strengthens women's subordination. This research will use Roland Barthes' semiotic analysis method. The theories that will be used in this research are the Male Gaze theory and Objectification Theory. The research results show that there is a visualization of women as objects of sexual fantasy and identified erotic exploitation, representing patriarchal culture and the commercialization of women's bodies.